2023
DOI: 10.3390/pathogens12040526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Diagnostic Potential of Chorismate Mutase Poly-Clonal Peptide Antibody for the Acanthamoeba Keratitis in an Animal Model

Abstract: Acanthamoeba spp. is the causative agent of Acanthamoeba keratitis (AK), a vision-threatening parasitic disease whose primary risk factor has been attributed to poor contact lens hygiene. Unfortunately, differential diagnosis of AK is challenging as the clinical manifestations for AK are similar to those of bacterial, fungal, or even viral keratitis. Since delayed AK diagnosis can incur permanent vision impairment, a rapid and sensitive diagnostic method is urgently needed. Here, the diagnostic potential of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The amoebae would normally be removed through the blinking action of the eyes [ 27 ]. Therefore, in previous AK animal infection models, to prevent this mechanism from causing failure in establishing the infection model, the eyelids of the infected animals were surgically sutured after administering the infection [ 28 ]. However, this additional suturing to prevent model induction failure due to blinking likely induces stress and physiological pressure on the infected animals, which could further alter their immune response and affect the infection rate of the inoculated Acanthamoeba .…”
Section: Discussionmentioning
confidence: 99%
“…The amoebae would normally be removed through the blinking action of the eyes [ 27 ]. Therefore, in previous AK animal infection models, to prevent this mechanism from causing failure in establishing the infection model, the eyelids of the infected animals were surgically sutured after administering the infection [ 28 ]. However, this additional suturing to prevent model induction failure due to blinking likely induces stress and physiological pressure on the infected animals, which could further alter their immune response and affect the infection rate of the inoculated Acanthamoeba .…”
Section: Discussionmentioning
confidence: 99%
“…These potential targets for antibodies may aid in diagnosis in the future: inosine-uridine preferring nucleoside hydrolase (IPNH), chorismite mutase (CM), carboxylesterase, adenylyl cyclaseassociated protein (ACAP), and periplasmic binding protein (PBP) [65][66][67][68][69]. Additional studies have demonstrated the utility of CM and ACAP/PBP antibodies in AK diagnosis in mouse and rabbit animal models, respectively [69,70]. Antibody-based tests hold potential in the diagnosis of AK but still require further investigation and development prior to their widespread use.…”
Section: Antibodymentioning
confidence: 99%